Clinical Cardiogenetics - Baars, H.F.; Doevendans, P.A.F.M.; van der Smagt, J.J.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
Clinics for cardiogenetic disorders have been established in many academic teaching hospitals in Europe. In these clinics, cardiologists, clinical and molecular geneticists, genetic nurses, and social workers closely cooperate to provide optimal care for individuals with cardiac disease of probable genetic origin and their family members. However, the prevalence of genetic cardiomyopathies and primary electrical heart diseases is sufficiently high, that it is neither desirable nor possible that the care for this group of patients and their relatives remains solely restricted to a small number of academic centers. Therefore basic knowledge on the genetic aspects of these types of disorders and on what to do with as yet asymptomatic at-risk family members should be considered to be a prerequisite for all practising cardiologists. Many cardiologists have not been specifically trained in genetics, let alone in explaining genetics to their patients. Clinical Cardiogenetics compiles the massive amount of information available in a single easy to read textbook. It does not require prior expert genetic knowledge and provides a practical clinical primer for cardiologists and other physicians involved in the management of these patients. With the continuing increase in genetic knowledge, and the expanding possibilities to prevent fatal arrhythmias in those individuals at high risk, a steady increase in questions regarding genetics from patients and their relatives in the years to come should be expected. This comprehensive textbook is a valuable tool in dealing with such questions.
Section I: BASIC CONCEPTS - Introduction, Introduction to molecular genetics, Molecular genetics in cardiology, Clinical Genetics of cardiac diseases -- Section II: CARDIOMYOPATHY - Hypertrophic cardiomyopathy -- Dilated cardiomyopathy, Arrhythmogenic Right Ventricular Cardiomyopathy, Other cardiomyopathies -- Section III: PRIMARY ELECTRICAL HEART DISEASES - Congenital long QT-syndrome, Brugada syndrome, Short QT-syndrome, Catecholamine induced polymorphic ventricular tachycardia, Familial atrial fibrillation, Hereditary conduction diseases, Connective tissue disorders and smooth muscle disorders, Genetics of congenital heart diseases, Genetics of hypertension and clinical aspects, Genetics of the lipoprotein metabolism and clinical aspects, Genetics of homocysteine metabolism and clinical aspects, Genetic markers of hemostatic factors, The pharmacogenetics of atherosclerosis, Genetics of (premature) coronary artery disease, Cardiac involvement in hereditary neuromuscular diseases, Sudden cardiac death < 40 years, The outpatient clinic for cardiogenetics, The future of cardiogenetics.
Keywords: Medicine; Human genetics; Internal medicine; Cardiology; Medicine & Public Health; Cardiology; Human Genetics; Internal Medicine